Identification and Spatiotemporal Characteristic Analysis of Compound Weather and Climate Extremes for Maize in Different Climate Zones of the Songliao Plain - Ziyuan Zhou; Ying Guo; Dan Chen; Kaiwei Li; Rui Wang; Xiao Wei; Jiquan Zhang; Chunli Zhao; Zhijun Tong; Xingpeng Liu (International Journal of Disaster Risk Science)
Abstract Due to global climate anomalies, the intensity and spatial extent of weather and climate extremes have increased notably. Therefore, extreme events must be studied to ensure agricultural production. In this study, the growing season accumulated temperature above 10 °C (GSAT10) was used as the climate regionalization index for maize in the Songliao Plain region, and the study area was divided into three climate zones. The standardized precipitation requirement index (SPRI) and standardized temperature index (STI) were introduced to analyze the spatial and temporal patterns of drought, waterlogging, and heat during the maize growing season from May to September using meteorological station data from the Songliao Plain between 1991 and 2020. The compound event magnitude indices were constructed by modeling the marginal distribution to detect the patterns of compound drought and heat events (CDHEs) and compound waterlogging and heat events (CWHEs), and to assess their potential impacts on maize production. The results show that: (1) The major meteorological disasters in the Songliao Plain region were drought and heat. The areas with prolonged high temperatures were similar to the areas with higher severity of temperature extremes, and were mainly concentrated in the central and southern parts of the study area (Zone 3). (2) The CWHEs mainly occurred in the northern part of the study area (Zones 1 and 2), and the CDHEs predominantly occurred in the central and southern parts of the study area. (3) For most sites on the Songliao Plain, the duration, severity, and intensity of compound extreme events were positively correlated with relative meteorological yield (Y w). Maize yield reduction was significantly affected by the CDHEs.